2013
DOI: 10.1094/pdis-01-13-0024-re
|View full text |Cite
|
Sign up to set email alerts
|

Presymptomatic Fibrous Root Decline in Citrus Trees Caused by Huanglongbing and Potential Interaction with Phytophthora spp.

Abstract: Huanglongbing (HLB), associated with ‘Candidatus Liberibacter asiaticus’, was first detected in Florida in late 2005 and is now widely distributed throughout the commercial citrus-growing regions. In recent seasons, concurrent with freeze and drought episodes, symptomatic HLB-infected trees were much more affected by the extremes of temperature and moisture than trees without HLB. Symptoms exhibited by the stressed trees were excessive leaf loss and premature fruit drop even when HLB-infected trees were manage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 130 publications
(131 citation statements)
references
References 23 publications
5
125
0
1
Order By: Relevance
“…L. asiaticus in the roots prior to leaf symptom development could be very instrumental in planning Phytophthora prevention measures as it was reported that prior infection of Ca. L. asiaticus promotes Phytophthora growth and subsequent damage to fibrous roots causing root decline (Graham et al, 2013); this is very important in Texas where Phytophthora inoculum is widespread (Timmer, 1972). Moreover, Trivedi et al (2010Trivedi et al ( , 2012 reported that the relative composition of the rhizosphere microbial community is affected and changed due to HLB infection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…L. asiaticus in the roots prior to leaf symptom development could be very instrumental in planning Phytophthora prevention measures as it was reported that prior infection of Ca. L. asiaticus promotes Phytophthora growth and subsequent damage to fibrous roots causing root decline (Graham et al, 2013); this is very important in Texas where Phytophthora inoculum is widespread (Timmer, 1972). Moreover, Trivedi et al (2010Trivedi et al ( , 2012 reported that the relative composition of the rhizosphere microbial community is affected and changed due to HLB infection.…”
Section: Discussionmentioning
confidence: 99%
“…This study also revealed that there was an enhancement of LB-induced symptoms by P. parasitica in citrus trees. Moreover, it was recently reported that HLB causes pre-symptomatic fibrous root decline, which was observed independently of Phytophthora (Graham et al, 2013). Detection of Ca.…”
Section: Introductionmentioning
confidence: 97%
“…The lower production of photosyntates, together with the reduction of its transport to other organs, especially the root, is likely to affect the overall vigor of the tree. Although the effect of disease in root density has not been studied, it is presumed that the amount of tree roots decreases in tres affected by the disease, as suggested by Graham et al (2013).…”
Section: Cuadro 1 Número De Frutos Por Mmentioning
confidence: 99%
“…Es probable que la menor producción de fotosintatos, junto con la reducción en su transporte hacia otros órganos, especialmente la raíz, afecte el vigor general del árbol. Aunque no se ha estudiado el efecto de la enfermedad en la densidad de raíces, se presume que la cantidad de raíces disminuye en árboles afectados por la enfermedad, como lo sugiere Graham et al (2013).…”
Section: Fruit Production In Trees With Different Level Of Affectatiounclassified
“…In Florida citrus production, the neonicotinoid insecticides imidacloprid (Admire ProÔ, Bayer Crop Science) and thiamethoxam (THIA, Platinum Ô , Syngenta Crop Protection) are applied as soil drenches to non-bearing trees for the control of citrus leafminer (Phyllocnistis citrella) and the associated infection of leafminer galleries by Xcc (Rogers, 2012). Systemic neonicotinoids are even more important for reducing transmission by the psyllid vector (Diaphorina citri) of Candidatus Liberibacter asiaticus (Las), the causal agent of Huanglongbing (HLB) disease (Graham et al, 2013b). HLB was first detected in Florida in late 2005 and is now widely distributed throughout the commercial citrus-growing regions (Gottwald, 2010).…”
Section: Introductionmentioning
confidence: 99%